Developing integrated piezoelectric direct current sensor with actuating and sensing elements. (1st December 2013) - Wang, Dong F.; Suzuki, Yasuhiro; Kobayashi, Takeshi; Itoh, Toshihiro; Maeda, Ryutaro
Abstract : A cantilever‐based, oscillating type MEMS direct current sensor (abbreviated as DC sensor), integrated with both actuating and sensing piezoelectric plates, as well as a micromagnet is proposed to satisfy the increasing needs of DC power supply for monitoring electrical consumption by either a single‐wire or two‐wire appliance cord. A prototype MEMS DC sensor, with a measured resonant frequency of 23 Hz, was microfabricated and characterised. In the case of a two‐wire electrical appliance cord, it was found that the change in the peak‐to‐valley value (abbreviated as P‐V value) of the output voltage was approximately proportional to the applied DC, and increased from 10.4 to 43.2 mV when the DC increased from 0 to 2 A under an excitation voltage of 5 Vpp. The shift of the resonant frequency because of the applied DC is believed to account for the change in the P‐V value (or the maximum value) of the output voltage. In summary, the proposed MEMS DC sensor integrated with both actuating and sensing piezoelectric plates was observed to measure the output voltage constantly and linearly over the applied DC directly in a two‐wire appliance without using a cord separator.